Determinants of Neonatal seizure among newborns attending a tertiary care Hospital (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Neonatal seizure is an important cause of childhood mortality and morbidity. The prevalence of neonatal seizure is 2-3 /1000 live births in term and 10-15 /1000 preterm deliveries in our country. Proper neonatal care is crucial. Different study results representing the risk factors for neonatal seizure are directly and indirectly related. Objectives: The study was carried out to determine the factors influencing neonatal seizure among the patients attending a tertiary care hospital. Methods: A cross- sectional study was carried out to find out the factors of neonatal seizure where face to face interview was taken to 50 purposively selected respondents who were attending a tertiary care hospital during spring season. All the data were entered into a personal computer and thoroughly checked for any possible errors and then processed and analyzed by statistical Package for Social Science (SPSS) version 17 and MS office 2007. Results: Among the total respondents mostly were of 37weeks.The study also reported that antenatal care by doctors was taken in 64% cases. Among the delivery related factors, most of the deliveries took place at home (64%). Among the neonatal factors weight 0.05). Association of onset of seizure and birth weight of the neonates also revealed insignificant (p>0.05) result. This can be explained by small sample size and short duration of study. On the other hand other studies reported significant (p